Violence and Grief in Ahmed Saadawi’s Frankenstein in Baghdad - Raheem, Lailan (Technische Universität Dortmund, 2024)
This thesis examines the portrayal of violence and grief in Ahmed Sa’adawi’s Frankenstein in Baghdad (2013) and explores their implications in post-invasion Iraq. Tracing Iraq’s history throughout the past four decades shows that one cannot skip the topics of war, death, and loss. Thus, this novel reflects a broader trend among Iraqi authors who use literature to give a voice to the silenced and forgotten victims of war. Sa’adawi’s work, blending elements of horror, magical realism, and political satire, stands out as one of the few Iraqi works that successfully reached Western audiences and received international acclaim, partly because of its intriguing title, which evokes Mary Shelley’s Frankenstein. Sa’adawi’s Frankensteinian figure is a stitched-up corpse that becomes inhabited by a lost soul. Driven by vengeance on behalf of the previous owners of his body parts, he commits a series of crimes that stir the media. These events take place two years after the American invasion, during the onset of a brutal sectarian war. This research investigates how this figure and other characters, such as Hadi and Elishva, navigate grief and violence and the extent to which the “Whatsitname” or Shisma is a manifestation of collective grief, especially within the historical context of Iraq. In addition, it offers a transcultural analysis that makes use of historical, political, literary, and cultural theoretical perspectives to examine the interconnection between grief and violence by drawing on theories by Judith Butler, Giorgio Agamben, and Achille Mbembe, and others. For instance, Butler’s concepts of grievability and precariousness will be applied to examine which lives are deemed mournable in the context of war. Agamben’s notion of “bare life” will frame the analysis of characters existing in a state of exception, while Mbembe’s work on necropolitics will contextualise the pervasive conflict in Iraq. This theoretical background will be enhanced by incorporating secondary literature, which will provide additional depth to the analysis. This comprehensive study aims to contribute to the understanding of contemporary Iraqi literature and its role in highlighting the aftermath of prolonged conflict, while also engaging with broader theoretical discussions on grief and violence in post-colonial contexts. The research also seeks to shed light on the cyclical nature of violence portrayed in the novel and its influence in shaping the socio-political reality after several years of conflict.
Keywords: 700